Can Business Rights Alleviate Group-Based Inequality in Sub-Saharan Africa? Understanding the Limits to Reform. Issue 3 (4th March 2019) - Taylor, Scott D.
Abstract: Africa's indigenous minorities face unique constraints, particularly in terms of engaging in even the most basic business activities. They typically lack business rights, but, even where such rights have been extended, they have had scant impact on group poverty. This paper argues that the failure of business rights to meaningfully transform the livelihoods of marginalised minority groups stems from elite capture of resources, dependency on external validation, and a contradiction between a collective problem (group poverty) and an individualist solution (business rights). African states could alter conditions through active pursuit of affirmative action policies, but lack socio-economic and political incentives.